150 Liquid Chromatography-Mass Spectrometry-Based Serum Metabolomics Analysis of the Effect of Dietary Energy Intake on the Onset of Puberty in Gilts. (7th December 2018) - Shi, M
Abstract: he objective of this study was to investigate the effect of deficient or surplus dietary energy intake on onset of first estrus in gilts and the differential serum metabolites analyzed by liquid chromatography-mass spectrometry (LC-MS) metabolomics. A total of 72 Landrace × Large White crossbred gilts (Body weight, 84.0 ± 2.4 kg; Age, 150.4 ± 3.5 day) were used. Gilts were assigned to one of the three dietary treatments consisting of net energy values at 9.5, 10.4 and 11.2 MJ/kg, which represented deficient (DE), adequate (AE) and surplus (SE) dietary energy concentration, respectively. Our results indicated that the gilts fed AE diet showed their first estrus about 7 days earlier than the gilts fed DE or SE diet ( P < 0.05). The LH pulse of gilts fed the DE diet was significantly lower than gilts fed the AE and SE diets ( P < 0.05). Gilts fed the SE diet had the lowest serum leptin concentration ( P < 0.01) compared with other treatments. Principal component analysis (PCA) of the serum metabolites showed distinct separation among the three groups. Compared with the AE group, gilts fed the DE diet displayed a persistent decline in phosphatidyl-ethanolamides (PE) and PE-Ceramide (PEC), while the gilts fed the SE diet displayed a persistent decline included phophatidyl-linositols (PI), sphinganine, and ceramide. In conclusion, inadequate or excess energy intake delayed the onset of first estrus in gilts, and the lower LH pulse or leptin concentration mainly accounts for this delay.